The commons in feminine. Body and power facing the expropriation of the economies for life - Quiroga Díaz, Natalia (2014)
The authors take the perspective of feminist Federici (2010) and her work on the role played by the witch hunt and the expropriation of knowledge and the female body in the initial stages of modern capitalism, as well as the perspective of feminists Gutiérrez (2013) and Segato (2010), who reflect on the Latin American exploitation of the commons and the enclosure of an economy oriented towards the care of life as something private and feminine, in order to find how the new current expropriation modalities are repeated or show differences. The authors will also discuss the current phase of capitalist accumulation and the subsumption of new common territories and resources and analyze how new enclosures point to social reproduction, in particular women´s bodies and areas of power. As a comparison, the 2001 Argentine crisis will be used as an example of a communitisation process of social resources based on popular management mechanisms.